Adhesive composition and metal composite film containing same
By using a follower layer composed of polypolyols with different glass conversion temperatures in aluminum-plastic films, the problem of breaking the deformation limit of aluminum-plastic films in extreme environments is solved, and the stable performance within a wide temperature range is achieved. Improve elasticity and toughness.
Patent Information
- Application Number
- CN202411709901.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
AI Technical Summary
When the existing aluminum-plastic film meets the strict requirements of high depth, high strength, high weather resistance and high heat resistance of power battery soft bags, there is a problem of breaking the deformation limit and causing rupture.
Using a follower composition, including a first polypolyol and a second polypolyol, the glass conversion temperature Tg1 of the first polyol is greater than the glass conversion temperature Tg2 of the second polyol, through such a combined follower layer , improve the adhesive performance and environmental resistance of aluminum-plastic film.
It achieves stable performance within a wide operating temperature range, improves the elasticity and toughness of aluminum-plastic film, and avoids the risk of rupture in extreme environments.
Smart Images

Figure CN119432295A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of production of outer packaging materials for batteries, in particular to an outer layer adhesive for high-performance aluminum-plastic films with high formability, high strength and high weather resistance. Background Art
[0002] Aluminum-plastic film is generally composed of three layers of films with different functions. The outer layer is composed of polyamide (hereinafter referred to as PA) or polyethylene terephthalate (hereinafter referred to as PET) alone or a composite of the two to form an outer protective layer. The middle layer is composed of aluminum foil of different thicknesses as a barrier layer and the inner layer is composed of thermoplastic resin. The layers are bonded by inner layer adhesive and outer layer adhesive respectively. Aluminum-plastic film with this structure is mostly used in small battery soft packs such as 3C, electronic cigarettes, button batteries, round batteries, etc., which plays a role in isolating and protecting the inside of the battery.
[0003] In recent years, with the strong rise of the electric vehicle industry, automobiles have increasingly higher requirements for battery lightweight, strength and other performance. Conventional aluminum-plastic films can no longer meet the stringent requirements of power batteries for soft-packs such as high punch depth, high strength, high weather resistance and high heat resistance. Compared with the metal shell of commonly used square shell batteries, aluminum-plastic film soft-pack batteries have the advantages of light weight and good ductility. When the internal cells of soft-pack batteries have "air bulging" phenomenon, the aluminum-plastic film can provide sufficient buffer space for the gas due to its excellent ductility. Before reaching the battery explosion threshold, the aluminum-plastic film will be torn, avoiding the possibility of battery explosion and protecting lithium-ion batteries well. Summary of the invention
[0004] If the deformation of the aluminum-plastic film is too large and exceeds its deformation limit, it will cause rupture. The deformation limit depends on the structural stability of the aluminum foil and the outer layer stacked on each other. As the adhesive between the aluminum foil and the outer layer, its bonding performance is particularly tested under the premise of meeting the above requirements.
[0005] In order to overcome the limitations of existing technologies and meet current market demands, one object of the present invention is to provide an adhesive composition, comprising: a first polyol; and a second polyol, wherein the glass transition temperature Tg1 of the first polyol is greater than the glass transition temperature Tg2 of the second polyol.
[0006] As mentioned above, in the adhesive composition, the number average molecular weight Mn1 of the first polyol is ≤10000, The number average molecular weight Mn2 of the second polyol is >10000.
[0007] As mentioned above, the hydroxyl value h1 of the first polyol is 5 to 50 mgOH / g. The hydroxyl value h2 of the second polyol is 5 to 50 mgOH / g, wherein h1>h2.
[0008] As mentioned above, for the adhesive composition, Tg1≥40°C and Tg2≤0°C.
[0009] As mentioned above, the adhesive composition
[0010] The first polyol includes polyoxyalkylene polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, polyamide polyol, polyester polyamide polyol, acrylic polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, ethylene-butylene copolymer polyol, polyisoprene polyol, hydrogenated polyisoprene polyol, polyvinyl butyral, polyvinyl formal or polyvinyl alcohol; the second polyol includes polyoxyalkylene polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, polyamide polyol, polyester polyamide polyol, acrylic polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, ethylene-butylene copolymer polyol, polyisoprene polyol, hydrogenated polyisoprene polyol, polyvinyl butyral, polyvinyl formal or polyvinyl alcohol.
[0011] The adhesive composition as described above further includes a third polyol having a number average molecular weight Mn3≤5000 and a glass transition temperature Tg3, wherein Tg2 <Tg3<Tg1。
[0012] As mentioned above, the adhesive composition, Mn3 <Mn1。
[0013] As mentioned above, the hydroxyl value h1 of the first polyol is 5 to 50 mgOH / g. The hydroxyl value h2 of the second polyol is 5 to 50 mgOH / g, and the hydroxyl value h3 of the third polyol is 100 to 150 mgOH / g, wherein h3>h1>h2.
[0014] As mentioned above in the adhesive composition, the third polyol includes any one of aliphatic polyol, alicyclic polyol or aromatic polyol or a combination of at least two thereof.
[0015] As mentioned above, the adhesive composition further includes isocyanate, which is selected from any one of aliphatic polyisocyanate, alicyclic polyisocyanate or aromatic polyisocyanate or a combination of at least two thereof, and the mass percentage of NCO is 10 to 30%.
[0016] Another object of the present invention is to provide a metal composite film, comprising: an intermediate metal layer; an outer substrate resin layer, arranged on one side of the intermediate metal layer; and an outer adhesive layer, arranged between the outer substrate resin layer and the intermediate metal layer, wherein the outer adhesive layer includes the adhesive composition as described above.
[0017] As described above, for the metal composite film, the outer substrate resin layer includes: a first outer resin layer; an adhesive layer, disposed between the first outer resin layer and the outer adhesive layer; and a second outer resin layer, disposed between the adhesive layer and the outer adhesive layer, wherein the adhesive layer includes the adhesive composition as described above.
[0018] The adhesive composition provided by the present invention has a relatively high molecular chain movement temperature and a relatively wide chain segment relaxation interval, has a transition peak in the low temperature range, and particularly exhibits more than two secondary transition peaks, indicating that the adhesive composition has good elasticity or toughness in different temperature ranges and can maintain stable performance within a wide working temperature range. Description of the Drawings
[0019] Figures 1A to 1B It is a cross-sectional view for explaining the laminate structure of the metal composite film.
[0020] (1): Outer substrate resin layer; (2): Outer adhesive layer; (3): Intermediate metal layer; (1a): First outer resin layer; (1b): Adhesive layer; (1c): Second outer resin layer; (4): Inner adhesive layer, (5): Inner heat-sealing resin layer. Detailed Embodiments
[0021] The following describes the detailed embodiments of the present invention with several examples and accompanying drawings. The first embodiment of the present invention is an adhesive composition, which includes a first polyol and a second polyol, wherein, the glass transition temperature Tg1 of the first polyol is greater than the glass transition temperature Tg2 of the second polyol.
[0022] Common to multiple examples, Tg1≥40°C, preferably 50°C<Tg1<80°C, more preferably 60°C<Tg1<75°C; Tg2 is preferably ≤0°C, preferably -40°C≤Tg2≤-10°C, more preferably -28°C≤Tg2≤-13°C.
[0023] Generally speaking, an adhesive with a high Tg has a higher degree of rigidity and is more suitable for high temperature environments, but it is difficult to avoid brittleness at low temperatures. Although a low Tg adhesive can maintain good flexibility in a low temperature environment, it is also inevitable that it will be overly softened at high temperatures. By combining the first polyol with a high Tg and the second polyol with a low Tg, the adhesive composition of the present invention has a wide operating temperature range and better environmental resistance, ensuring the adhesion strength, elasticity and toughness at different temperatures.
[0024] The molecular weight of the main component of the adhesive will directly affect its viscosity and the impact resistance, ductility and other properties after curing. In order to meet the above performance requirements, the first polyol and the second polyol are configured with different molecular weights; specifically, there is no special restriction on the number average molecular weight (Mn) of the first polyol and the second polyol, but the number average molecular weight Mn1 of the first polyol ≤ 10000 is more ideal, especially 3000-8000, and further 4000-6000 is more ideal; the number average molecular weight Mn2 of the second polyol> 10000 is ideal, especially 10000-50000, and further 12000-30000 or 14000-20000 is more ideal.
[0025] Considering the adhesion of the adhesive composition, the hydroxyl value h1 of the first polyol is preferably 5 to 50 mgOH / g, preferably 5 to 20 mgOH / g, and more preferably 9 to 13 mgOH / g; the hydroxyl value h2 of the second polyol is preferably 5 to 50 mgOH / g, preferably 5 to 15 mgOH / g, and more preferably 5.5 to 9 mgOH / g. Among them, h1>h2.
[0026] Commonly used in multiple embodiments, the first polyol can be listed as: polyoxyalkylene polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, polyamide polyol, polyester polyamide polyol, acrylic polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, ethylene-butene copolymer polyol, polyisoprene polyol, hydrogenated polyisoprene polyol, polyvinyl butyral or polyvinyl formal, polyvinyl alcohol; preferably, the first polyol is a polyester polyol.
[0027] Commonly used in multiple embodiments, the second polyol can be listed as: polyoxyalkylene polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, polyamide polyol, polyester polyamide polyol, acrylic polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, ethylene-butene copolymer polyol, polyisoprene polyol, hydrogenated polyisoprene polyol, polyvinyl butyral, polyvinyl formal or polyvinyl alcohol; preferably, the second polyol is a polyurethane polyol.
[0028] Common to multiple embodiments, the mass ratio of the first polyol to the second polyol is (28-48):(28-52), preferably (29-35):(29-35).
[0029] In some embodiments, the adhesive composition further comprises a third polyol having a glass transition temperature Tg3, where Tg2 < Tg3 < Tg1; preferably, -10°C < Tg3 ≤ 0°C, more preferably -6.5°C ≤ Tg3 ≤ 4.5°C.
[0030] In these embodiments, the number average molecular weight Mn3 of the third polyol is ≤ 5000, and Mn3 < Mn1; Preferably, Mn3 ≤ 2000, more preferably 1000 ≤ Mn3 ≤ 1500.
[0031] In these embodiments, the hydroxyl value h3 of the third polyol is preferably 100 to 150 mgOH / g, Preferably 105 to 130 mgOH / g, more preferably 110 to 120 mgOH / g, where h3 > h1 > h2.
[0032] In these embodiments, the mass ratio of the first polyol, the second polyol, and the third polyol is (28 - 48):(28 - 52):(13 - 16), preferably (29 - 35):(29 - 35):(14 - 16).
[0033] In these embodiments, the third polyol includes any one or a combination of at least two of aliphatic polyols, alicyclic polyols, or aromatic polyols; preferably, the third polyol is a graft polymer.
[0034] In these embodiments, the third polyol is specifically a polyester polyol formed by polymerizing a dibasic acid and a diol.
[0035] In the case of aliphatic polyols, examples of the dibasic acid include any one or a combination of at least two of adipic acid, azelaic acid, and sebacic acid, and examples of the diol that can be used include: ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,3 - propanediol, dipropylene glycol, tripropylene glycol, 1,4 - butanediol, 1,5 - pentanediol, neopentyl glycol, 1,6 - hexanediol, 1,7 - heptanediol, 1,2 - octanediol, or any one or a combination of at least two of them or a diol having an alkane chain with C9 to C20 as the main chain.
[0036] In these embodiments, in the case of alicyclic polyols, examples of the dibasic acid include any one or a combination of at least two of adipic acid, azelaic acid, and sebacic acid, and examples of the diol that can be used include: 1,4 - cyclohexanediol, 1,3,3 - trimethylcyclohexane - 1,2 - diol, 1 - methylcyclohexane - 1,4 - diol, [1,1'-bis(cyclohexane)] - 2,2'-diol, 1,4 - cyclohexanedimethanol, 1,2 - cyclohexanedimethanol, 2-(4-propylcyclohexyl)-1,3-propanediol, any one thereof or a combination of at least two thereof.
[0037] In these embodiments, as for the aromatic polyol, the dibasic acid may be any one of phthalic acid, isophthalic acid, and terephthalic acid, or a combination of at least two thereof; the diol may be ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,3-propylene glycol, dipropylene glycol, tripropylene glycol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,7-heptanediol, 1,2-octanediol, any one or a combination of at least two thereof or a main chain of C9 to C20 alkane chain diol.
[0038] Preferably, the third polyol includes one or more of adipic acid-ethylene glycol-1,4-butanediol polyester polyol, adipic acid-1,4-butanediol polyester polyol, adipic acid-neopentyl glycol polyester polyol, and adipic acid-1,6-hexanediol polyester polyol, and more preferably adipic acid-1,4-butanediol polyester polyol.
[0039] Generally applicable to the above embodiments, the adhesive composition further comprises isocyanate, and the NCO mass percentage thereof is 10 to 30%, preferably 15 to 20%, and more preferably 17 to 20%, based on the total mass of the isocyanate. to 18%.
[0040] The type of the isocyanate is not particularly limited, and may be any one of aliphatic polyisocyanate, alicyclic polyisocyanate or aromatic polyisocyanate, or a combination of at least two of them.
[0041] Preferably, the isocyanate comprises an aromatic polyisocyanate, and the following can be cited for use: toluene diisocyanate (TDI), TDI-trimer, diphenylmethane diisocyanate, Any one or a combination of at least two of TDI-TMP; more preferably, the isocyanate is toluene diisocyanate.
[0042] In some embodiments, the mass ratio of the first polyol, the second polyol and the isocyanate is (28-48):(28-52):(5-8), preferably (29-35):(29-35):(7-8); in other embodiments, the mass ratio of the first polyol, the second polyol, the third polyol and the isocyanate is (28-48):(28-52):(13-16):(19-23), preferably (29-35):(29-35):(14-16):(20-22).
[0043] A second embodiment of the present invention is an outer packaging material for a lithium ion battery device, comprising at least one metal composite film (100), such as Figures 1A to 1B As shown, it is a laminate consisting of at least an outer base resin layer (1), an outer adhesive layer (2), an intermediate metal layer (3), an inner adhesive layer (4) and an inner heat-melting resin layer (5).
[0044] Common to multiple embodiments, the specific structure of the metal composite film (100) includes: Intermediate metal layer (3); An outer base material resin layer (1) is disposed on one side of the intermediate metal layer (3); The outer adhesive layer (2) is disposed between the outer base resin layer (1) and the intermediate metal layer (3), wherein the outer adhesive layer (2) comprises the adhesive composition provided in the first embodiment.
[0045] The intermediate metal layer (3) is an aluminum alloy foil. In addition to aluminum (ALM), the aluminum alloy foil also contains iron (Fe), silicon (Si), copper (Cu), zinc (Zn), and titanium (Ti). The specific thickness can be 10 to 50 μm, and the surface wettability is 10 to 100 dyn / cm. Preferably, the intermediate metal layer (3) is made of 8021 Aluminum alloy foil made from aluminum.
[0046] In some embodiments, Figure 1B As shown, the outer substrate resin layer (1) may include: A first outer resin layer (1a); An adhesive layer (1b) is disposed between the first outer resin layer (1a) and the outer adhesive layer (2); The second outer resin layer (1c) is disposed between the adhesive layer (1b) and the outer adhesive layer (2), wherein the adhesive layer (1b) comprises the adhesive composition provided in the first embodiment.
[0047] Specifically, the resins used to form the first outer resin layer (1a) and the second outer resin layer (1c) include: polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin and other resins or modified products of the aforementioned resins. They can be copolymers of these resins, modified products of copolymers, or mixtures of these resins. More specifically, the first outer resin layer (1a) is a polyester layer, and the second outer resin layer (1c) is a polyamide layer.
[0048] Examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, and copolyesters. In addition, copolyesters include copolyesters with ethylene terephthalate as the main repeating unit. More specifically, copolymer polyesters (hereinafter referred to as copolyesters (terephthalate / ethylene isophthalate)) are obtained by polymerizing ethylene terephthalate as the main repeating unit. isophthalate)), copolyester (terephthalate / adipate), copolyester (terephthalate / sodium isophthalate), copolyester (terephthalate / phenyl-dicarboxylate), copolyester (terephthalate / decane dicarboxylate), etc.; the above polyesters can be used alone or in combination. Use in combination of the above.
[0049] Examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; or isophthalic acid structural units such as nylon 6I, nylon 6T, nylon 6I T, nylon 6I6T (I represents isophthalic acid, T represents terephthalic acid), hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamide, polyamide MXD6 (polyamide PACM6 (polybis(4-aminocyclohexyl)methaneazideamide)) and the like; the above polyamides may be used alone or in combination of two or more.
[0050] Preferably, the second outer resin layer (1c) is a biaxially oriented nylon film with polyamide as the basic material. The thickness is preferably 10 to 30 μm.
[0051] In some embodiments, Figures 1A to 1B As shown, the metal composite film (100) further comprises: an inner heat-welding resin layer (5) disposed on the other side of the intermediate metal layer (3) relative to the outer base resin layer (1); and An inner adhesive layer (4) is provided between the intermediate metal layer (3) and the inner heat-melting resin layer (5) between.
[0052] Specifically, the material of the inner adhesive layer (4) is not particularly limited, and examples of the materials that can be used include: polyolefin, cyclic polyolefin or modified polyolefin, wherein the modified polyolefin can be carboxylic acid-modified polyolefin, carboxylic acid-modified cyclic polyolefin, methacrylic acid-modified polyolefin, acrylic acid-modified polyolefin, crotonic acid-modified polyolefin or imide-modified polyolefin; in some examples, the material of the inner adhesive layer (4) can also be formed by coating the adhesive composition provided in the first embodiment on the intermediate metal layer (3) and curing it.
[0053] As for the resin constituting the inner heat-melting resin layer (5), there is no particular restriction as long as it is a heat-melting material that can exert heat-melting properties when assembling the battery and is used to seal the battery assembly. Resins containing a polyolefin main chain, such as polyolefins and acid-modified polyolefins, are preferred.
[0054] Example 1 :
[0055] 1. Preparation and performance testing of adhesive composition
[0056] The adhesive composition is synthesized from polyester polyol (hereinafter referred to as resin 1), polyurethane modified polyol (hereinafter referred to as resin 2) and aliphatic polyol, alicyclic polyol or aromatic polyol (hereinafter referred to as resin 3), and toluene diisocyanate (TDI), wherein the number average molecular weight Mn1 of resin 1 is 4500, the hydroxyl value h1 is 10.85 mgOH / g, and the glass transition temperature Tg1 is 71.12°C; the number average molecular weight Mn2 of resin 2 is 15500, the hydroxyl value h2 is 8 mgOH / g, and the glass transition temperature Tg2 is -13.45°C; the number average molecular weight Mn3 of resin 3 is 1300, the hydroxyl value h3 is 116.23 mgOH / g, and the glass transition temperature Tg3 is -5.15°C; The NCO content of TDI is 17.43%; in terms of mass, the ratio of resin 1: resin 2: resin 3: TDI is 31.3: 31.3: 15.7: 21.7; the above raw materials are mixed according to the ratio and stirred at room temperature until they are evenly mixed.
[0057] 1.1. Film physical property test
[0058] Pour the mixed adhesive composition into a 10*10cm PP dish and level it naturally, vacuum degassing, The film was cured at 80° C. for 3 days to form a film with a thickness of about 50 μm, which was then cut into strips with a width of 1.5 mm and a length of 20 mm and tested using a dynamic mechanical analyzer (DMA) with a tensile fixture.
[0059] DMA test conditions: measured at a frequency of 110 Hz and a temperature change rate of 2°C / min.
[0060] The DMA test results show that the loss factor tanδ of the film is 87.2°, and the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤7.71℃, and the two secondary transition peaks are located at -38.59℃ and -74.53℃ respectively.
[0061] In addition, the film was cut into strips with a width of 15 mm and a length of 75 mm, and placed on a tensile testing machine with a tensile gauge length fixed at 50 mm. The relative humidity was controlled at 50% ± 5%. When the tensile test was performed at a speed of 50 mm / min, its breaking strength, elongation at break, modulus, and yield strength were measured.
[0062] The breaking strength of the film is 35.0Mpa, the breaking elongation is 361%, the modulus is 573Mpa, and the yield strength is 47.3Mpa.
[0063] 2. Preparation and performance testing of metal composite films
[0064] In this embodiment, a metal composite film is prepared by a lamination method, specifically a laminate consisting of an outer substrate resin layer (1), an outer adhesive layer (2), an intermediate metal layer (3), an inner adhesive layer (4) and an inner heat-melting resin layer (5).
[0065] The outer substrate resin layer (1) is a laminate composed of a first outer resin layer (1a), an adhesive layer (1b) and a second outer resin layer (1c), wherein the first outer resin layer (1a) is a biaxially stretched film with a thickness of 25 μm prepared from polyester, and the second outer resin layer (1c) is a biaxially stretched nylon film with a thickness of 25 μm prepared from amide, and the adhesive layer (1b) is formed by coating the aforementioned adhesive composition on the second outer resin layer (1c), covering the first outer resin layer (1a) on the adhesive composition, and then curing it.
[0066] The intermediate metal aluminum layer (3) is made of 8021 series aluminum material with a surface wettability of 68 dyn / cm, pressed into an aluminum foil with a thickness of 40 μm; it is particularly noted that before starting the laminate composite process, both sides of the intermediate metal aluminum layer (3) are first subjected to anti-corrosion treatment to form an anti-corrosion layer, and the anti-corrosion layer is formed by applying an anti-corrosion liquid on both sides of the intermediate metal aluminum layer (3) and drying it, wherein the anti-corrosion liquid is composed of chromium phosphate, nitric acid, and polypropylene resin in a mass ratio of 2:2:1.
[0067] The adhesive composition is applied to any surface of the intermediate metal layer (3) and dried to form an outer adhesive layer (2) with a thickness of 3 μm. Then, at a temperature of 90°C, a 25 μm outer base resin layer (1) is covered on the outer adhesive layer (2), wherein the outer base resin layer (1) is compounded by contacting the second outer resin layer (1c) with the outer adhesive layer (2), and then an aging treatment is performed at a temperature of 80°C for 5 days to form an outer base resin layer (25 μm) / outer adhesive layer (2). A semi-finished metal composite film of adhesive layer (3μm) / intermediate metal layer (40μm); subsequently, the aforementioned adhesive composition is coated on the other side of the intermediate metal layer relative to the outer adhesive layer, and after drying, a 3μm inner adhesive layer is formed, which is then compounded with an inner heat-melting resin film at 120±5°C to form a metal composite film of outer base resin layer (25μm) / outer adhesive layer (3μm) / intermediate metal layer (40μm) / inner adhesive layer (3μm) / inner heat-melting resin layer.
[0068] 2.1. Peel strength test
[0069] The prepared metal composite film was cut into strips with a width of 15 mm and a length of 75 mm. A T-type peeling test was performed at a test speed of 50 mm / min in an environment with a relative humidity of 50±5%. The peel strengths of the second outer resin layer (1c) and the intermediate metal aluminum layer (3) at temperatures of -40°C, 120°C, and 23°C were measured, and the peel strengths were 6.7N, 4.8N, and 8.9N, respectively.
[0070] 2.2. Weathering performance test
[0071] The same size of the sample was stored in pure water at 85℃ for 7 days and then at 23℃. In an environment with a relative humidity of 50±5%, T-type peeling was performed at a test speed of 50 mm / min, and the peel strength between the second outer resin layer (1c) and the intermediate metal aluminum layer (3) at a temperature of 23° C. was 6.6N.
[0072] 2.3. Forming performance test
[0073] The metal composite film was subjected to deep punching and forming, and the forming speed of the forming machine was set to 5 mm / s and 7 mm / s, and the punching depths were 10.50 mm and 8.75 mm respectively.
[0074] Embodiment 2:
[0075] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 1, except that: The mass ratio of resin 1:resin 2:resin 3:TD I is 32.9:29.7:15.6:21.8.
[0076] The test items and operations are the same as those in Example 1.
[0077] The DMA test results of the film show that tanδ is 82.6°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤8.32℃, and the two secondary transition peaks are located at -41.26℃ and -73.82℃ respectively; in addition, the film has a breaking strength of 33.5Mpa, an elongation at break of 346%, a modulus of 554Mpa, and a yield strength of 43.2Mpa.
[0078] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.3N, 4.1N, and 8.2N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 6.3N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 10.50mm and 8.50mm, respectively.
[0079] Example 3
[0080] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 1, except that: The mass ratio of resin 1:resin 2:resin 3:TD I is 33.4:31.8:14.3:20.6.
[0081] The test items and operations are the same as those in Example 1.
[0082] The DMA test results of the film show that tanδ is 84.5°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤9.42℃, and the two secondary transition peaks are located at -43.70℃ and -74.11℃ respectively; in addition, the film has a breaking strength of 34.1Mpa, an elongation at break of 335%, a modulus of 546Mpa, and a yield strength of 46.4Mpa.
[0083] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.4N, 4.5N, and 8.6N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 5.8N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 10.50mm and 8.50mm, respectively.
[0084] Embodiment 4:
[0085] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 1, except that: The mass ratio of resin 1:resin 2:resin 3:TD I is 29.8:32.9:15.7:21.7.
[0086] The test items and operations are the same as those in Example 1.
[0087] The DMA test results of the film show that tanδ is 89.8°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤7.32℃, and the two secondary transition peaks are located at -38.57℃ and -77.32℃ respectively; in addition, the film has a breaking strength of 36.3Mpa, an elongation at break of 357%, a modulus of 567Mpa, and a yield strength of 49.0Mpa.
[0088] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.8N, 4.9N, and 9.6N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 6.1N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 10.50mm and 9.00mm, respectively.
[0089] Example 5 :
[0090] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 1, except that: The mass ratio of resin 1:resin 2:resin 3:TD I is 31.8:33.4:14.3:20.5.
[0091] The test items and operations are the same as those in Example 1.
[0092] The DMA test results of the film show that tanδ is 88.0°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤7.63℃, and the two secondary transition peaks are located at -41.99℃ and -75.82℃ respectively; in addition, the film has a breaking strength of 34.7Mpa, an elongation at break of 348%, a modulus of 571Mpa, and a yield strength of 48.5Mpa.
[0093] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.4N, 4.3N, and 8.3N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 5.9N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 10.50mm and 8.75mm, respectively.
[0094] Example 6 :
[0095] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 1, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: resin 3: TDI is 31.4: 31.4: 15.7: 21.5.
[0096] The test items and operations are the same as those in Example 1.
[0097] The DMA test results of the film show that tanδ is 79.8°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤11.08℃, and the two secondary transition peaks are located at -36.28℃ and -88.13℃ respectively; in addition, the film has a breaking strength of 38.5Mpa, an elongation at break of 389%, a modulus of 587Mpa, and a yield strength of 48.2Mpa.
[0098] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.8N, 5.1N, and 9.2N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 6.5N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 10.50mm and 8.50mm, respectively.
[0099] Embodiment 7:
[0100] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 2, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: resin 3: TDI is 33.5:31.9:14.4:20.3.
[0101] The test items and operations are the same as those in Example 2.
[0102] The DMA test results of the film show that tanδ is 83.3°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤13.26℃, and the two secondary transition peaks are located at -33.89℃ and -86.45℃ respectively; in addition, the film has a breaking strength of 37.2Mpa, an elongation at break of 376%, a modulus of 563Mpa, and a yield strength of 48.7Mpa.
[0103] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.5N, 4.9N, and 8.9N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 6.5N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 10.50mm and 8.75mm, respectively.
[0104] Embodiment 8:
[0105] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 3, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: resin 3: TDI is 29.9:33.0:15.7:21.4.
[0106] The test items and operations are the same as those in Example 3.
[0107] The DMA test results of the film show that tanδ is 84.5°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤12.99℃, and the two secondary transition peaks are located at -34.93℃ and -88.58℃ respectively; in addition, the film has a breaking strength of 38.1Mpa, an elongation at break of 395%, a modulus of 563Mpa, and a yield strength of 47.2Mpa.
[0108] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.6N, 4.7N, and 8.6N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 6.3N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 11.00mm and 8.75mm, respectively.
[0109] Embodiment 9:
[0110] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 4, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: resin 3: TDI is 31.9:33.5:15.7:21.4.
[0111] The test items and operations are the same as those in Example 4.
[0112] The DMA test results of the film show that tanδ is 82.9°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤11.65℃, and the two secondary transition peaks are located at -33.48℃ and -87.56℃ respectively; in addition, the film has a breaking strength of 39.1Mpa, an elongation at break of 371%, a modulus of 592Mpa, and a yield strength of 49.0Mpa.
[0113] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.3N, 5.0N, and 9.3N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 6.4N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 10.50mm and 8.50mm, respectively.
[0114] Embodiment 10:
[0115] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 5, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: resin 3: TDI is 31.9:33.5:14.4:20.2.
[0116] The test items and operations are the same as those in Example 5.
[0117] The DMA test results of the film show that tanδ is 81.8°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤12.04℃, and the two secondary transition peaks are located at -35.1℃ and -86.67℃ respectively; in addition, the film has a breaking strength of 37.5Mpa, an elongation at break of 373%, a modulus of 587Mpa, and a yield strength of 48.3Mpa.
[0118] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 6.1N, 4.6N, and 9.0N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 5.9N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the punching depths were 11.00mm and 8.50mm, respectively.
[0119] Comparative Example 1:
[0120] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Example 1, except that: The adhesive-free composition does not contain resin 3, and the mass ratio of resin 1:resin 2:TD I is 41.52:50.75:7.73.
[0121] The test items and operations are the same as those in Example 1.
[0122] The DMA test results of the film show that tanδ is 65.4°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤47.60℃, and there is only one secondary transition peak at -15.74℃; in addition, the film has a breaking strength of 28.6Mpa, an elongation at break of 221%, a modulus of 376Mpa, and a yield strength of 36.5Mpa.
[0123] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 1.1N, 2.8N, and 7.4N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 4.9N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 8.75mm and 6.00mm, respectively.
[0124] Comparative Example 2:
[0125] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 1, except that: The mass ratio of resin 1:resin 2:TD I is 46.08:46.98:7.84.
[0126] The test items and operations are the same as those of Comparative Example 1.
[0127] The DMA test results of the film show that tanδ is 69.4°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤43.50℃, and there is only one secondary transition peak located at -13.76℃; in addition, the film has a breaking strength of 27.6Mpa, an elongation at break of 254%, a modulus of 385Mpa, and a yield strength of 38.2Mpa.
[0128] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 0.9N, 3.1N, and 7.6N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 5.2N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 8.75mm and 6.25mm, respectively.
[0129] Comparative Example 3:
[0130] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 1, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: TDI is 41.77:51.05:7.17.
[0131] The test items and operations are the same as those of Comparative Example 1.
[0132] The DMA test results of the film show that tanδ is 71.3°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤49.90℃, and there is only one secondary transition peak at -14.01℃; in addition, the film has a breaking strength of 29.3Mpa, an elongation at break of 264%, a modulus of 381Mpa, and a yield strength of 39.3Mpa.
[0133] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 1.0N, 3.3N, and 7.7N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 5.1N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 8.75mm and 5.75mm, respectively.
[0134] Comparative Example 4:
[0135] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 2, except that: The number average molecular weight Mn2 of resin 2 is 18900, the hydroxyl value h2 is 6.7 mgOH / g, and the glass transition temperature Tg2 is -27.6°C; the mass ratio of resin 1: resin 2: TDI is 46.33:46.33:7.33.
[0136] The test items and operations are the same as those of Comparative Example 2.
[0137] The DMA test results of the film show that tanδ is 72.8°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤48.73℃, and there is only one secondary transition peak at -13.03℃; in addition, the film has a breaking strength of 28.4Mpa, an elongation at break of 259%, a modulus of 361Mpa, and a yield strength of 37.4Mpa.
[0138] In the peel strength test results of the metal composite film, the peel strengths at temperatures of -40°C, 120°C, and 23°C were 1.1N, 3.0N, and 7.4N, respectively; the weather resistance test showed that the peel strength after being stored in 85°C pure water for 7 days was 5.3N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 8.75mm and 6.00mm, respectively.
[0139] Comparative Example 5:
[0140] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 1, except that: The glass transition temperature Tg2 of resin 2 is 71.12°C.
[0141] The test items and operations are the same as those of Comparative Example 1.
[0142] The DMA test results of the film show that tanδ is 60.4°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤45.1℃, and there is only one secondary transition peak at -9.5℃; in addition, the film has a breaking strength of 19.3Mpa, an elongation at break of 159%, a modulus of 234Mpa, and a yield strength of 33.3Mpa.
[0143] In the peel strength test results of the metal composite film, the peel strengths at temperatures of 120°C and 23°C were 0.8N and 5.6N respectively, and could not be measured at -40°C; the weather resistance test showed that the peel strength after being stored in pure water at 85°C for 7 days was 2.4N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 6.00mm and 4.00mm respectively.
[0144] Comparative Example 6:
[0145] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 2, except that: The glass transition temperature Tg1 of resin 1 is -13.45°C.
[0146] The test items and operations are the same as those of Comparative Example 2.
[0147] The DMA test results of the film show that tanδ is 56.1°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤39.7℃, and there is only one secondary transition peak at -7.31℃; in addition, the film has a breaking strength of 18.7Mpa, an elongation at break of 163%, a modulus of 224Mpa, and a yield strength of 31.9Mpa.
[0148] In the peel strength test results of the metal composite film, the peel strengths at temperatures of 120°C and 23°C were 0.7N and 5.3N respectively, and could not be measured at -40°C; the weather resistance test showed that the peel strength after being stored in pure water at 85°C for 7 days was 2.3N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 5.75mm and 4.00mm respectively.
[0149] Comparative Example 7:
[0150] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 3, except that: The glass transition temperature Tg2 of resin 2 is 71.12°C.
[0151] The test items and operations are the same as those of Comparative Example 3.
[0152] The DMA test results of the film show that tanδ is 66.3°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤40.23℃, and there is only one secondary transition peak at -10.4℃; in addition, the film has a breaking strength of 18.5Mpa, an elongation at break of 161%, a modulus of 247Mpa, and a yield strength of 35.6Mpa.
[0153] In the peel strength test results of the metal composite film, the peel strengths at temperatures of 120°C and 23°C were 1.1N and 5.5N respectively, and could not be measured at -40°C; the weather resistance test showed that the peel strength after being stored in pure water at 85°C for 7 days was 2.4N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 6.25mm and 4.50mm respectively.
[0154] Comparative Example 8:
[0155] The preparation method of the adhesive composition and the metal composite film is substantially the same as that of Comparative Example 4, except that: The glass transition temperature Tg1 of resin 1 is -27.6°C.
[0156] The test items and operations are the same as those of Comparative Example 4.
[0157] The DMA test results of the film show that tanδ is 45.5°, the absolute value of the tanδ half-amplitude corresponding to the temperature range is ≤38.56℃, and there is only one secondary transition peak at -14.5℃; in addition, the film has a breaking strength of 17.8Mpa, an elongation at break of 148%, a modulus of 228Mpa, and a yield strength of 30.7Mpa.
[0158] In the peel strength test results of the metal composite film, the peel strengths at temperatures of 120°C and 23°C were 0.5N and 4.8N respectively, and could not be measured at -40°C; the weather resistance test showed that the peel strength after being stored in pure water at 85°C for 7 days was 1.9N; the molding performance test showed that under the conditions of molding machine molding speeds of 5mm / s and 7mm / s, the pit depths were 6.00mm and 3.75mm respectively.
[0159] The test results of the film properties of the above Examples 1 to 10 and Comparative Examples 1 to 8 are summarized in Table 1a below. Table 1a
[0160] As can be seen from Table 1a, the adhesive compositions prepared in Examples 1 to 10 have a larger transition peak near 90°C and exhibit a higher tanδ, which means that the molecular chain movement temperature of the adhesive composition is higher, giving the film higher elasticity and strength, while the narrower tanδ half-width reflects that the loss range of the adhesive composition during the transition process is smaller, the material transformation is concentrated and fast, and the film is given sufficient rigidity; multiple secondary transition peaks reflect that there are multiple different movement modes in the molecular structure of the adhesive composition material, such as the movement of the side chain of the molecular main chain vibration, the movement of the group or the internal rotation of the side chain group, which can show a wider range of elasticity or toughness in different temperature ranges; taking these characteristics into consideration, the film exhibits excellent breaking strength, breaking elongation, elastic film content and yield strength.
[0161] The performance test results of the metal composite films of Examples 1 to 10 and Comparative Examples 1 to 8 are summarized in Table 1b below. Table 1b
[0162] As shown in Table 1b, the metal composite films coated with Examples 1 to 10 as the outer adhesive layer, Due to the combination of polyester diols with different Tg, it can still have a considerable level of peel strength in extreme environments, and can also maintain a considerable level of peel strength after being exposed to high temperature environments for a certain period of time, showing that it has good weather resistance. On the contrary, even if polyester diols with different molecular weights are used to provide a considerable degree of molecular chain movement space for the outer adhesive layer, under the condition of the same resin Tg, although it can still maintain a certain peel strength at room temperature, the peel strength in extreme environments (-40°C) cannot be measured, indicating that it has lost its bonding ability.
[0163] In addition, the impact speed range of the metal composite film's impact resistance has also been greatly expanded, which can adapt to the punching speed and punching requirements of different battery factories; according to the time-temperature equivalence principle, when the punching speed is slow, it is equivalent to placing the metal composite film in a high-temperature environment for molding. At this time, the high-Tg polyester diol provides sufficient cohesive strength to ensure that the metal composite film is formed without cracking; when the punching speed is fast, the low-Tg polyester diol molecular chain has a larger stretching space, which can also ensure the punching and pitting of the metal composite film.
[0164] In summary, the present invention ensures that the metal composite film has excellent heat resistance, structural strength, adhesion and formability by simultaneously controlling the molecular weight of the polyester diol in the adhesive composition and matching different glass transition temperatures; this is because the high molecular weight ensures that the adhesive composition has sufficient strength and molecular chain elongation, providing the necessary strength extension during deep punching, and the high Tg can stabilize the internal structure of the adhesive layer at high working temperatures; the low Tg exhibits good flexibility at normal temperatures and provides low temperature resistance, and the low molecular weight acts as a toughening agent, providing the adhesive layer with extension space through the real-time dislocation between the molecular chains at high punching rates, so that the metal composite film can withstand a sufficiently large punching depth.
[0165] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.
[0166] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. An adhesive composition, characterized in that: include: a first polyol; and The second polymeric polyol, wherein the glass transition temperature Tg1 of the first polymeric polyol is greater than the glass transition temperature Tg2 of the second polymeric polyol.
2. The adhesive composition according to claim 1, characterized in that The number average molecular weight Mn1 of the first polyol is ≤10000, and the number average molecular weight Mn2 of the second polyol is >10000.
3. The adhesive composition according to claim 1, wherein The hydroxyl value h1 of the first polyol is 5 to 50 mgOH / g, and the hydroxyl value h2 of the second polyol is 5 to 50 mgOH / g, wherein h1>h2.
4. The adhesive composition according to claim 1, wherein Tg1≥40℃, Tg2≤0℃.
5. The adhesive composition according to claim 1, wherein: The first polyol comprises polyoxyalkylene polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, polyamide polyol, polyester polyamide polyol, acrylic polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, ethylene-butylene copolymer polyol, polyisoprene polyol, hydrogenated polyisoprene polyol, polyvinyl butyral polyvinyl formal or polyvinyl alcohol; The second polyol includes polyoxyalkylene polyol, polyester polyol, polycarbonate polyol, polyurethane polyol, polyamide polyol, polyester polyamide polyol, acrylic polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, ethylene-butene copolymer polyol, polyisoprene polyol, hydrogenated polyisoprene polyol, polyvinyl butyral, polyvinyl formal or polyvinyl alcohol.
6. The adhesive composition according to claim 1, wherein: Further comprising a third polyol having a number average molecular weight Mn3≤5000 and a glass transition temperature Tg3, wherein Tg2 <Tg3<Tg1。 7. The adhesive composition according to claim 6, characterized in that: Mn3 <Mn1。 8. The adhesive composition according to claim 6, wherein: The hydroxyl value h1 of the first polyol is 5 to 50 mgOH / g, the hydroxyl value h2 of the second polyol is 5 to 50 mgOH / g, and the hydroxyl value h3 of the third polyol is 100 to 150 mgOH / g, wherein h3>h1>h2.
9. The adhesive composition according to claim 6, wherein: The third polyol includes any one of aliphatic polyol, alicyclic polyol or aromatic polyol, or a combination of at least two of them.
10. The adhesive composition according to claim 1, wherein The isocyanate is further comprised of any one or a combination of at least two of aliphatic polyisocyanate, alicyclic polyisocyanate or aromatic polyisocyanate, and the mass percentage of NCO is 10 to 30%.
11. A metal composite film, characterized in that: include: Intermediate metal layer; An outer base resin layer is disposed on one side of the intermediate metal layer; and The outer adhesive layer is disposed between the outer base resin layer and the intermediate metal layer, wherein the outer adhesive layer comprises the adhesive composition according to any one of claims 1 to 10.
12. The metal composite film according to claim 11, characterized in that: The outer substrate resin layer comprises: a first outer resin layer; an adhesive layer disposed between the first outer resin layer and the outer adhesive layer; and The second outer resin layer is disposed between the adhesive layer and the outer adhesive layer, wherein the adhesive layer comprises the adhesive composition according to any one of claims 1 to 10.